Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Karakter Kemandirian Peserta Didik Pada Mata Pelajaran Matematika Kelas III SDN 167 Pekanbaru - Juliana Juliana; Sakban Sakban; Deprizon Deprizon (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the learning independence of class III students at SDN 167 Pekanbaru in mathematics learning before and after using inquiry strategies. This research is classroom action research using the Kemmis and Taggart method, namely (plan, action, observation and reflection). This research consists of 2 cycles, each with 2 meetings. Data collection techniques use observation, field notes and documentation. Data analysis uses quantitative and qualitative. Research results: In the Pre-Cycle, most students were in the Less Independent category. Entering Cycle I, there is a clear improvement. The number of students in the Sufficiently Independent category has increased, but there are still students in the Less Independent category. In Cycle II, the most striking changes occurred. The number of students in the Very Independent category increased significantly. This shows that the majority of students now have a high level of independence, with great achievements in increasing their independence compared to the previous cycle.